2021
DOI: 10.15581/003.34.2.449-468
|View full text |Cite
|
Sign up to set email alerts
|

Legitimation of hate and political violence through memetic images: the Bolsonaro campaign

Abstract: The federal elections were held in Brazil in 2018. The ballot resulted in a victory for the far-right candidate, Jair Messias Bolsonaro. The question that arose after the victory of the far-right was: How could this have happened? One of the instruments that undoubtedly contributed to this unexpected victory was a peculiar aspect of his political campaign: memetic communication. Through the use of memes in the social media (above all WhatsApp), Bolsonaro’s project transformed these violent discourses against p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…18-19) o crear conciencia. Aunque en ocasiones las imágenes pueden banalizar y legitimar la violencia (Villanueva y Bayarri, 2021), también pueden desencadenar un efecto de responsabilidad en el espectador (Belli y Fernández Villanueva, 2021, p. 7).…”
Section: Nudgesunclassified
“…18-19) o crear conciencia. Aunque en ocasiones las imágenes pueden banalizar y legitimar la violencia (Villanueva y Bayarri, 2021), también pueden desencadenar un efecto de responsabilidad en el espectador (Belli y Fernández Villanueva, 2021, p. 7).…”
Section: Nudgesunclassified
“…However, Bolsonaro's rhetoric had always been characterised by violence and stigmatisation. Diverse studies have shown how this violent rhetoric was articulated towards women (Pinheiro‐Machado & de Freixo, 2019) and the Afro‐descendant population (Fernández‐Villanueva & Bayarri, 2021), using stigmatisation, animalisation and hyalinisation: black people were represented as obese and dirty, transsexuals as an aberration, and feminists were associated with communism. All of this came together to produce a ‘political enemy’ with respect to the traditional, heterosexual, white family, and established a strong and appealing heteronormativity as part of the Bolsonaro construction of the ‘real’ citizen entitled to civil rights.…”
Section: Key Moments In the Construction Of Bolsonarismomentioning
confidence: 99%
“…In order to achieve their political desires, people often find people doing various ways to bring down their political opponents. Hatred of political opponents is often found in the campaign arena (Fernández Villanueva & Bayarri Toscano, 2021).…”
Section: Introductionmentioning
confidence: 99%